2020
DOI: 10.1002/adom.202000897
|View full text |Cite
|
Sign up to set email alerts
|

Rare‐Earth Metal Ions Doped Graphene Quantum Dots for Near‐IR In Vitro/In Vivo/Ex Vivo Imaging Applications

Abstract: Near‐infrared (NIR) emitting biocompatible nanomaterials are desired in biotechnology as higher penetration depth fluorescence imaging probes. In this work, novel NIR‐emissive Nd3+‐doped or Tm3+‐doped biocompatible graphene quantum dots (GQDs) are developed via scalable, single‐step bottom‐up synthesis. Water‐soluble Nd‐GQDs/Tm‐GQDs with average diameters of 5.6–8.2 nm possess crystalline graphene lattice with <1 atomic percent of Nd/Tm and exhibit NIR fluorescence at ≈1060/≈925 nm attributed to the intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 53 publications
(68 reference statements)
1
44
0
1
Order By: Relevance
“…Some researchers are interested in the development of carbon points emitting red fluorescence and their application in near-infrared biological imaging [95][96][97]. Li et al attached electron acceptor groups (rich in sulfoxide/carbonyl groups) to the outer layer and edges of the CDs.…”
Section: Cds In Biotargeting and Bioimagingmentioning
confidence: 99%
“…Some researchers are interested in the development of carbon points emitting red fluorescence and their application in near-infrared biological imaging [95][96][97]. Li et al attached electron acceptor groups (rich in sulfoxide/carbonyl groups) to the outer layer and edges of the CDs.…”
Section: Cds In Biotargeting and Bioimagingmentioning
confidence: 99%
“… The NIR fluorescence of GQDs showed excellent performance due to their remarkable attributes such as the deep penetration depth, nonblinking fluorescence emission, facile spatiotemporal control, good water solubility, and biocompatibility. Feng et al, for the first time, reported the two-photon (TP) behavior of GQDs with an NIR emission at 660 nm upon excitation with 810 nm femtosecond pulses having a cross-section of 25.12 GM . The developed nanoprobe using CoOOH-NIR GQDs (N-GQDs) was successfully applied to detect ascorbic acid (AA) in living cells as well as deep-tissue imaging .…”
Section: Attributes Of Graphene Quantum Dotsmentioning
confidence: 99%
“…In comparison, GQDs with diameters ranging from 0.89 to 1.80 nm emit fluorescence covering the entire visible light spectrum range (400–770 nm) [ 246 ]. The NIR fluorescence of GQDs showed excellent performance due to their remarkable attributes such as deep penetration depth, unblinking fluorescence emission, easy spatiotemporal control, good water solubility, and biocompatibility [ 247 , 248 ].…”
Section: Reviewmentioning
confidence: 99%